Emerging Phenomena of the Branded App: A Systematic Literature Review, Strategies, and Future Research Directions. Issue 2 (4th May 2019) - Mondal, Jalaluddin; Chakrabarti, Somnath
Abstract: Marketers are increasingly adopting the branded app as a strategy to communicate with, engage with, and sell a product to consumers. This study assesses this emerging research theme and its future research directions by adopting the systematic literature review approach and identifying 40 peer-reviewed research papers published since 2008. Using content analysis, the authors highlight several trends and insights, such as field of research, research design, and sampling technique, along with various prevailing constructs, underpinning theories, and research outcomes. The authors' contribution lies, first, in categorizing branded app extant research into five subthemes: branded app design, branded app adoption, consumer usage and retention, consumer–brand engagement, and consequences of adoption; second, in describing the branded app by breaking it down into four marketing concepts (product, service, media, and marketing tool) to show the integration of existing theories in branded app research whereby 25 existing theories have been used 37 times in branded app research. Further, as its original contribution, the authors conceptualize a new framework on branded app strategy and identify future research directions.